"That Night": Unlocking the Memories of Loss on Canvey Island in 1953. (3rd July 2018) - Armstrong, Stephanie; Easthope, Lucy
ABSTRACT: The need to tell or correct a narrative about a totemic moment in the history of a place is brought to the fore in this article. It tells the story of a series of meetings in 2015 with older residents of Canvey Island in Essex who had asked for a chance to share individual experiences of 'that night' of flooding in 1953. A need to seize one last chance to tell the story, or tell it for the first time, is found in the recollections of other older people experiencing traumatic events. The article details the gathering of profound and painful narratives that had previously remained hidden and were fragile to loss forever. It reflects on the importance of protecting the older persons' narrative when gathering collective memory. The events at the heart of the narratives occurred in 1953 but their potency is not diminished by the passing of time.